A step towards environmental performance metrics for transportation – A case study at Mölnlycke Health Care - Mulvet, Aurelia (My University, 2013)
Logistics managers face increasing demand to consider the environment in decision making. Yet, there is no standardised procedure to assess the environmental impact of transport systems. The purpose of this thesis is to contribute to the environmental performance management research with metrics that fulfil both operational reporting and managerial decision requirements. The thesis has an abductive approach and is based on primary data collected through interviews and questionnaires. Performance management is the main theory of concern. The focus of this thesis lies upon the pre-analysis and pre-design of an environmental performance management system for freight transport operations at Mölnlycke Health Care, which includes three sections: 1) metrics, 2) calculations, and 3) dashboard. Empirical findings are analysed through a gap analysis and are compiled in a manner which allows the finalised results to be presented in a dashboard. The main conclusion incites further data collection from transport services providers to increase accuracy and transparency in order to initiate the implementation of environmental performance management systems for transportation. Further research to link environmental performance to financial performance, and behavioural change from organisations, are also suggested.
Keywords: Produktion; Transport; Övrig industriell teknik och ekonomi; Production; Transport; Other industrial engineering and economics